Struktur Nafkah pada Rumah Tangga Desa Agrowisata - Rahmah, Ulya; Saidah, Zumi; Yudha, Eka Purna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Agrotourism, developed in Alamendah Village since 2011, has opened new economic opportunities that have transformed the residents' livelihoods from agricultural activities to those related to the tourism sector. This study aims to examine the household livelihood structure in Alamendah Village, in relation to the presence of agrotourism in the area. The research design utilized is quantitative. The research methods employed are survey research and in-depth interviews using questionnaires as tools. The data analysis used in this study is descriptive statistical analysis and cross tabulation. The results show that the majority of farmers in Alamendah Village have low incomes, while traders have higher incomes. Agrotourism has the potential as an economic opportunity and a source of additional income that can help improve the local community's economy by considering factors such as age, education, and gender.